Analisis Potensi Peredaran Vaksin Corona Virus Disease-19 (COVID-19) Palsu di Indonesia - Rinukti, Ndaru Sindi; Rastika, Gede Bayu Rastika; Triwinanti, Neti (Badan Pengawas Obat dan Makanan, 2023)
During the COVID-19 pandemic, Indonesian government has done various efforts to overcome the spread of COVID-19 outbreak, some of them are by accelerating the procurement of COVD-19 vaccine and conducting vaccination in Indonesia. However, there are several potential threats that may occur, one of them is potential entry or production of falsified COVID-19 vaccines in Indonesia. This analysis identifies the potential distribution of falsified COVID-19 vaccines in Indonesia and strategic role of Indonesian Food and Drug Authority (Indonesian FDA) to prevent its distribution. This analysis applies qualitatitve methods by using literature review correlated with relevant case studies about the finding of falsified COVID-19. The result shows that falsified COVID-19 vaccines have been found in several countries such as China, Mexico, Poland, Uganda, India, Myanmar and Islamic Republic of Iran using various modes including promotion through internet. Furthermore, sales of used COVID-19 vaccine vial also found in internet especially in darkweb, which can increase the potential for counterfeiting COVID-19 vaccine. In Indonesia, the case of falsified vaccine occurred in 2016 for Measles Vaccine, Polio Vaccine, Hepatitis B Vaccine, Tetanus Vaccine, and BCG Vaccine by refilling empty used vaccine vial using intravenous infusion fluid and antibiotics. According to that case and conditions, the case of counterfeiting COVID-19 vaccine may occur in Indonesia either through the misuse of vial waste or using the other modes considering similar case in 2016. Indonesian FDA plays important role to ensure the integrity of COVID-19 vaccine supply chain, including its vial waste handling to prevent counterfeiting that endangers public health.